2019
DOI: 10.1038/s41594-019-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pharmacology of metabotropic receptors targeted by neuropsychiatric drugs

Abstract: Metabotropic receptors are responsible for so-called slow synaptic transmission and mediate the effects of 100's of peptide and non-peptide neurotransmitters and neuromodulators. Over the past decade or so a revolution in membrane protein structural determination has clarified the molecular determinants responsible for the actions of these receptors. Here I focus on the G protein-coupled receptors (GPCRs) which are targets for neuropsychiatric drugs and show how insights into the structure and function of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 136 publications
0
38
0
Order By: Relevance
“…), which is a GABA B agonist used in the treatment of muscle spasms. 41,42,[44][45][46] The family C GPCRs differ from others by possessing a large extracellular domain, distal to the TMD receptors, and containing the orthosteric sites; they also form constitutive dimers with unique activation systems in comparison with other GPCR families. 41 Similarly, to their related families, family C GPCRs exhibit a typical motif of seven TMD helices however differ structurally from other GPCR families in their possession of an unusually large extracellular domain, an intracellular carboxylterminal (C-terminal) domain and a heptahelical TMD (Fig.…”
Section: Family C (Metabotropic Glutamate Receptors)mentioning
confidence: 99%
“…), which is a GABA B agonist used in the treatment of muscle spasms. 41,42,[44][45][46] The family C GPCRs differ from others by possessing a large extracellular domain, distal to the TMD receptors, and containing the orthosteric sites; they also form constitutive dimers with unique activation systems in comparison with other GPCR families. 41 Similarly, to their related families, family C GPCRs exhibit a typical motif of seven TMD helices however differ structurally from other GPCR families in their possession of an unusually large extracellular domain, an intracellular carboxylterminal (C-terminal) domain and a heptahelical TMD (Fig.…”
Section: Family C (Metabotropic Glutamate Receptors)mentioning
confidence: 99%
“…This is remarkable considering that prospective VS campaigns often result in antagonists even when an agonist-bound VS model is used. 81 , 82 The distinct pharmacological profiles of MVC, compound 1 , and compound 3 need to be further assessed in functional assays.…”
Section: Discussionmentioning
confidence: 99%
“…After Cellular analysis it was revealed that this increase was due to enhanced expression of mGluR5 mRNA in pyramidal cells in lamina III of this area of prefrontal cortex. 24…”
Section: Metabotropic Receptorsmentioning
confidence: 99%